The linguistic components of intercultural communications on an example of a multicultural society: comparative studies of cultures - Akizhanova, Diana (2021)
Intercultural communication is considered a progressively developing trend, both abroad and in modern Russia. The concept of Western research on this topic is interdisciplinary approaches this situation is conditioned by the need for a multilateral analysis of the processes taking place in this field. Attention is focused on studying the barriers to communication of representatives of many socio-cultural systems. The information reflects the experience of using Western methodology to analyze the problems of intercultural interaction. The main barriers that reduce the effectiveness of interactions are the differences in cognitive schemes that are relevant for representatives of certain cultures (in particular linguistic and non-verbal schemes, moments of public consciousness). The results of the study do not allow the dissemination of conclusions to an extremely broad social context. But due to the experience of interpreting the problems of intercultural communication, information is useful for organizations that function in the field of education, as well as leading dialogue between Russia and the West. It was possible to identify approaches to the definition of intercultural communication as an important branch of knowledge in the context of globalization, analyzing domestic and foreign traditions. The factors that predetermine the effectiveness of communication, as well as methods for overcoming complexities in the course of intercultural communication, are listed. The approaches that form the basis of the process of preparing people for life and work in a multicultural society, in the context of intercultural communication, are at the center of attention. Thanks to the culture of communication, it is possible to achieve mutual understanding between different nations, to form national self-consciousness, as well as the effective development of traditional cultures. A valuable social function is to translate not just the national and ethnic culture, but also to introduce the younger generation to common values, the world cultural process, of which the culture of any people is considered a part. For this, a dialogue of cultures is established, inter-ethnic communication appears. Nowadays there are quite a lot of nationalistic tendencies explaining the desire of the ethnoses to revive and preserve, develop personal cultural traditions and language, and to establish modern culture at the personal and group level thanks to national forms and symbols.